PAX Genes in Cancer; Friends or Foes? - Eccles, Mike R.; Li, Caiyun G. (Frontiers in Genetics, 2012)
PAX genes have been shown to be critically required for the development of specific tissues and organs during embryogenesis. In addition, PAX genes are expressed in a handful of adult tissues where they are thought to play important roles, usually different from those in embryogenesis. A common theme in adult tissues is a requirement for PAX gene expression in adult stem cell maintenance or tissue regeneration. The connections between adult stem cell PAX gene expression and cancer are intriguing, and the literature is replete with examples of PAX gene expression in either situation. Here we systematically review the literature and present an overview of postnatal PAX gene expression in normal and cancerous tissue. We discuss the potential link between PAX gene expression in adult tissue and cancer. In addition, we discuss whether persistent PAX gene expression in cancer is favourable or unfavourable.